2019
DOI: 10.1007/s13197-018-3530-2
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, structural and functional properties of native and irradiated starch: a review

Abstract: The world population has crossed seven billion and such a huge population has increased the pressure and considerably affects our ability to feed ourselves. It has now emerged as a new challenge for policy makers, food scientists and other associated people to make food available to everyone. To achieve this, underutilized crops/plants that act as good sources of starch need to be explored. Starch in its native form have certain limitations in its functional properties to be used for different applications. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(58 citation statements)
references
References 52 publications
(93 reference statements)
2
46
0
2
Order By: Relevance
“…The oval shapes in the micrographs are the starch granules, which are surrounded by the protein, or fiber particles disrupted during the ball milling. Bashir and Aggarwal (2019), Chung and Liu (2010) and Gani et al (2012) have reported similar results for bean, chickpeas and other legumes.…”
Section: Scanning Electron Microscopementioning
confidence: 54%
“…The oval shapes in the micrographs are the starch granules, which are surrounded by the protein, or fiber particles disrupted during the ball milling. Bashir and Aggarwal (2019), Chung and Liu (2010) and Gani et al (2012) have reported similar results for bean, chickpeas and other legumes.…”
Section: Scanning Electron Microscopementioning
confidence: 54%
“…Simultaneously, no significant difference in the PV of HM rice under 1 and 2 kGy ( p < 0.05) irradiation was observed because the husks protected the rice grains from high irradiation doses. Electron beams destroy the interior structure of rice [ 26 ] and are likely to first act on water molecules [ 27 ]. Their action on a large number of water molecules results in the production of free radicals and a certain amount of thermal energy.…”
Section: Resultsmentioning
confidence: 99%
“…LM rice did not have the same taste as HM rice. Unsatisfactory rice taste might be ascribed to the production of undesirable flavors as a result of the following: irradiation produces free radicals, which break rice starch molecules [ 27 ], expose hydrophobic side chains inside proteins [ 35 ], and partially oxidize protein and fat. In general, the quality and taste of HM rice were superior to those of LM rice.…”
Section: Resultsmentioning
confidence: 99%
“…A wide range of native starches with profoundly different functionalities is required to meet market needs 1 , 2 . However, native starches have technological limitations 3 . Thus, there is substantial interest in modifying their structures to improve properties and increase starch application 4 .…”
Section: Introductionmentioning
confidence: 99%